2014
DOI: 10.1245/s10434-014-4183-7
|View full text |Cite
|
Sign up to set email alerts
|

Stratification of Contemporary Patients Undergoing Radical Prostatectomy for High-risk Prostate Cancer

Abstract: A significant heterogeneity existed in biochemical outcomes of contemporary patients with high-risk prostate cancer who underwent definitive RP. According to primary Gleason pattern and number of high-risk criteria present, high-risk group should be stratified further into favorable and unfavorable disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Our findings are similar to those of 2 single institution retrospective reviews of post-radical prostatectomy cases in which Gleason pattern 5 on biopsy was associated with biochemical recurrence. 18,19…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are similar to those of 2 single institution retrospective reviews of post-radical prostatectomy cases in which Gleason pattern 5 on biopsy was associated with biochemical recurrence. 18,19…”
Section: Discussionmentioning
confidence: 99%
“…To enhance the chance of long-term survival in high-risk patients, new treatment options including pre-surgical systemic chemotherapy, hormonal therapy, and targeted agents are being investigated [24]. A recent study suggested that high-risk patients undergoing RP should be further stratified based on primary Gleason pattern and the number of high-risk criteria [3]. By noninvasively providing metabolic information reflecting Gleason score and tumor volume, MRSI may have the ability to aid in substratification of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Candidates for radical prostatectomy (RP) may have clinically low, intermediate, or high-risk disease and further prognostic data would aid the physician making treatment decisions [2,3]. Proton MR spectroscopic imaging ( 1 H-MRSI) permits the analysis of metabolism as reflected by the levels of choline-containing compounds, polyamines (spermine and spermidine), creatine, and citrate in PCa [4].…”
Section: Introductionmentioning
confidence: 99%
“…The authors suggested stratification of patients with high-risk PCa into the following three subgroups: good prognosis subgroup (1 high-risk factor); intermediate prognosis subgroup (PSA level > 20 ng/ mL and stage cT3-4); and poor prognosis subgroup (Gleason score 8-10 in combination with at least 1 other high-risk factor). Because of the lack of a definition of high-risk PCa, studies have subclassified high-risk PCa into different prognostic categories [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…our study indicated which patients may require surgery and which patients may not require surgery. Most previous studies aimed to validate the subset of the high-risk group according to the oncological outcomes within each risk group [ 20 , 24 , 25 ]. The present study identified the oncological outcomes of each subgroup based on the number of risk factors after comparison with those in the other risk groups in patients with high-risk PCa.…”
Section: Discussionmentioning
confidence: 99%